Relationship between memory strategies and verbal memory impairments following left anterior temporal lobectomy - Miura, Kayoko; Koike, Atsushi; Adachi, Kouhei; Matsui, Mie; Baba, Hiroshi (Bulletin of Hokuriku Psychological Society of Japan, 2012)
In this study, we examined 1）characteristics of the memory strategy 2）relationship between memory strategy and verbal memory performance, in patients following left anterior temporal lobectomy. The participants were 11 patients （male 4, female 7） who had undergone left anterior temporal lobectomy. They were read unrelated word pairs in a Miyake Paired-Associate Word Learning Test. Subsequently, the first word of each pair was read and they were asked to recall the second word. After the recall session, the subjects were asked to indicate for each word the type of memory strategy they had used （visual imagery, verbal, verbal repetition, other, none）. Among the strategies reported, verbal repetition strategy was most frequent, but efficient memory strategies, like visual imagery strategy, were few. This finding suggests the possibility that impairments of verbal memory performance after left anterior temporal lobectomy were associated with the in efficient memory strategy. On the other hand, there was a significant positive correlation between the frequency of visual imagery strategy and the verbal memory performance. This indicates that using a lot of visual imagery strategy enhances memory performance in lobectomy patients.